Single particle tracking of internalized metallic nanoparticles reveals heterogeneous directed motion after clathrin dependent endocytosis in mouse chromaffin cells - Gabriel, Manuela (2018)
Most accepted single particle tracking methods are able to obtain high-resolution trajectories for relatively short periods of time. In this work we apply a straightforward combination of single-particle tracking microscopy and metallic nanoparticles internalization on mouse chromaffin cells to unveil the intracellular trafficking mechanism of metallic-nanoparticle-loaded vesicles (MNP-V) complexes after clathrin dependent endocytosis. We found that directed transport is the major route of MNP-Vs intracellular trafficking after stimulation (92.6% of the trajectories measured). We then studied the MNP-V speed at each point along the trajectory, and found that the application of a second depolarization stimulus during the tracking provokes an increase in the percentage of low-speed trajectory points in parallel with a decrease in the number of high-speed trajectory points. This result suggests that stimulation may facilitate the compartmentalization of internalized MNPs in a more restricted location such as was already demonstrated in neuronal and neuroendocrine cells (Bronfman et al 2003 J. Neurosci. 23 3209-20). Although further experiments will be required to address the mechanisms underlying this transport dynamics, our studies provide quantitative evidence of the heterogeneous behavior of vesicles mobility after endocytosis in chromaffin cells highlighting the potential of MNPs as alternative labels in optical microscopy to provide new insights into the vesicles dynamics in a wide variety of cellular environments.